Does the cardiovascular drug levosimendan prevent iodinated contrast medium nephrotoxicity with glycerol aggravation in rats? - Durur-Subasi, Irmak; Kose, Duygu; Yayla, Muhammed; Sirin, Busra; Karaman, Adem; Calik, Ilknur; Alper, Fatih (Springernature, 2021)
Background We investigated whether levosimendan prevents contrast medium nephrotoxicity with glycerol aggravation in rats. Methods Forty-eight Wistar albino rats were assigned to eight groups (n = 6 x 8). No medication was administered to group I (controls); glycerol (intramuscular injection of 25% glycerol, 10 mL/kg) group II; intravenous iohexol 10 mL/kg to group III; glycerol and iohexol to group IV; iohexol and intraperitoneal levosimendan 0.25 mg/kg to group V; glycerol, iohexol, and levosimendan 0.25 mg/kg to group VI; iohexol and levosimendan 0.5 mg/kg to group VII; and glycerol, iohexol, and levosimendan 0.5 mg/kg to group VIII. One-day water withdrawal and glycerol injection prompted renal damage; iohexol encouraged nephrotoxicity; levosimendan was administered 30 min after glycerol injection and continued on days 2, 3, and 4. The experiment was completed on day 5. Serum blood urea nitrogen (BUN) and creatinine levels, superoxide dismutase (SOD) activity, glutathione (GSH), malondialdehyde (MDA) levels, tumour necrosis factor-alpha (TNF-alpha), nuclear factor kappa ss (NFK-ss), interleukin 6 (IL-6), and histopathological marks were assessed. One-way analysis of variance and Duncan's multiple comparison tests were used. Results Levosimendan changed serum BUN (p = 0.012) and creatinine (p = 0.018), SOD (p = 0.026), GSH (p = 0.012), and MDA (p = 0.011). Levosimendan significantly downregulated TNF-alpha (p = 0.022), NFK-ss (p = 0.008), and IL-6 (p = 0.033). Histopathological marks of hyaline and haemorrhagic cast were improved in levosimendan-injected groups. Conclusion Levosimendan showed nephroprotective properties due to its vasodilator, oxidative distress decreasing and inflammatory cytokine preventing belongings.
Keywords: Contrast media; Drug-related side effects and adverse reactions; Iohexol; Levosimendan; Rats (Wistar)